Thogoto Virus Matrix Protein Is Encoded by a Spliced mRNA - Kochs, Georg (American Society for Microbiology, 2000)
Thogoto virus (THOV) is a tick-transmitted orthomyxovirus with a segmented, negative-stranded RNA genome. In this study, we investigated the coding strategy of RNA segment 6 and found that it contains 956 nucleotides and codes for the matrix (M) protein. The full-length cDNA contains a single, long reading frame that lacks a stop codon but has coding capacity for a putative 35-kDa protein. In contrast, the M protein of THOV has an apparent molecular mass of 29 kDa as assessed by polyacrylamide gel electrophoresis. Therefore, we investigated the possibility of posttranscriptional processing of segment 6 transcripts by reverse transcription-PCR and identified a spliced mRNA that contains a stop codon and is translated into the 29-kDa M protein. Interestingly, the nontemplated UGA stop codon is generated by the splicing event itself. Thus, the unusual M coding strategy of THOV resembles that of Influenza C virus.